Hibridismo e religiosidade na obra A herança de Mestre Bimba : filosofia e lógica africanas da capoeira de Mestre Decanio - Prado, Paulo César Almeida do (2022)
This work aims to present, from the analysis of the work A herança de mestre Bimba: filosofia e lógica africanas da capoeira – Master Bimba’s inheritance: philosophy and African logic of capoeira –, the interpretative work carried out by Ângelo Augusto Decanio Filho (Mestre Decanio) of religious elements from multiple traditions such as Candomblé, Zen Buddhism, Judaism and Christianity that generated a hybrid image of Capoeira Regional capable of overcoming the specific differences of each tradition and founding a discourse that culminated in an experience, in capoeira, of unity and ecstasy. In order to do so, we use, as theoretical tools, in addition to the works of Mestre Decanio, the reflections of authors such as Mikhail Bakhtin, Burke, P. Berger, Stuart Hall and H. Bhabha, aiming at foundamenting our reflection on the decanian work as an important milestone for studies on the relationship between culture and religiosity in the field of Sciences of Religion. Seeking a better exposition of the theme discussed here, we divided our analysis into three chapters to, finally, present some conclusions, in the form of openings, for possible works focused on the space of capoeira as a “place” of plurality and religious dynamism.